Plan de marketing para promocionar los lugares turísticos de las Parroquias del cantón Pangua año 2021 - Cutos Tigrero, Ariel Oswaldo (2021)
The current research was raised through a marketing plan to promote the tourist places that the parishes of the Pangua Canton of Cotopaxi province have, since this place has natural resources that allow promoting the development of tourism on a large scale. The objectives of the research is to analyze a marketing plan, the development of tourism in the canton, the identification of tourist activities and the creation of a guide or triptych with the attractions of the Pangua canton, therefore, it was identified through the type of research (surveys ) some tourist problems such as economic, lack of promotion, which obstructs progress in the growth of local tourism. In order to meet the objectives set out in this work, deductive and inductive methods will be used; The types applied in the research were documentaries, sources of information and surveys, which reached conclusions and recommendations with a focus such as the development of tourism; because today it is considered as another source of income for people dedicated to the area of tourism. The current authorities try to consolidate projects of great impact to grow tourism and consider the Pangua Canton as a tourist power of the Province of Cotopaxi.